2005
DOI: 10.1007/s10541-005-0169-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Biochemical Properties of DNA Methyltransferase FauIA Modifying the Second Cytosine in the Nonpalindromic Sequence 5′-CCCGC-3′

Abstract: A gene encoding DNA methyltransferase (methylase) FauIA of the restriction-modification system FauI from Flavobacterium aquatile (recognizing sequence 5'-CCCGC-3') was cloned in pJW vector. The latter was used for transformation of E. coli RRI cells followed by subsequent thermoinduction and biomass elaboration. Highly purified DNA methyltransferase FauIA preparation was obtained using chromatography on different sorbents. The molecular mass of the isolated enzyme of about 39 kD corresponds to its theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For example, it is reported that both methylases (LlaDII and Bsp6I R/M) have two recognition sites (5'-GCGGC-3' and 5'-GCCGC-3') [18]. DNA methyltransferase (methylase) FauIA (of the restriction-modification system FauI from Flavobacterium aquatile)'s recognization site is 5'-CCCGC-3' [19]. Our study offers a perspective to find a connection between the DNA sequence fragments and the methylation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it is reported that both methylases (LlaDII and Bsp6I R/M) have two recognition sites (5'-GCGGC-3' and 5'-GCCGC-3') [18]. DNA methyltransferase (methylase) FauIA (of the restriction-modification system FauI from Flavobacterium aquatile)'s recognization site is 5'-CCCGC-3' [19]. Our study offers a perspective to find a connection between the DNA sequence fragments and the methylation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown that 5 bp DNA lengths are important for DNA methylation where they are probably associated with the binding of DNA methyltransferase [29]. 5 bp long sequences are important for the binding of many enzymes including the methyltransferase; both methylases ( Lla DII and Bsp 6I R/M) have two recognition sites (5′-GCGGC-3′ and 5′-GCCGC-3′) [3-0] and 5′-CCCGC-3′ is the recognition site of the DNA methyltransferase (methylase) FauIA (of the restriction-modification system FauI from Flavobacterium aquatile ) [30]. …”
Section: Methodsmentioning
confidence: 99%